Supersessionism, the Epistle to the Romans, Thomas Aquinas, and the Jews of the Eschaton - Cohen, Jeremy (Journal of ecumenical studies, 2017)
Contemporary theologians, intent on divesting Christian theology of supersessionism, have sought to ground a more benign, more pluralistic ecclesiastical stance toward the Jews in Thomas Aquinas's Commentary on Romans. This essay returns to that Romans commentary in its medieval context, seeking to appreciate the ambiguities of the Jews' role in salvation history as Thomas construed it. Reviewing the modern literature and pre-modern sources, the essay thus takes issue with the reading of Thomas proffered by Bruce Marshall, Steven Boguslawski, Matthew Tapie, and others, and, recalling the counsel of Edward Synan, it proposes that the priorities of post-Holocaust, post-supersessionist theology not lure the historian into imposing upon Aquinas the values and priorities of an age not his own.